2015
DOI: 10.1111/odi.12341
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde production by major oral microbes

Abstract: The oral microbiota of orally healthy subjects comprises considerable amounts of bacteria possessing the ability to produce ACH, an oral carcinogen. Consumption of sugar alcohols may regulate ACH production by oral microbes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 31 publications
4
77
0
Order By: Relevance
“…Neisseria species, present in the saliva of ≥80% of the subjects in this study, have been reported to produce considerable amounts of ACH from ethanol in vitro [9,13]. However, the salivary microbiota with less relative abundance of Neisseria species (type I community) showed significantly higher ACH production ability than that with the higher relative abundance of Neisseria species (type II community).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Neisseria species, present in the saliva of ≥80% of the subjects in this study, have been reported to produce considerable amounts of ACH from ethanol in vitro [9,13]. However, the salivary microbiota with less relative abundance of Neisseria species (type I community) showed significantly higher ACH production ability than that with the higher relative abundance of Neisseria species (type II community).…”
Section: Discussionmentioning
confidence: 79%
“…These findings highlighted that the salivary microbiota with higher relative abundance for Neisseria species independently associated with lower ACH production ability, although Neisseria are oral bacterial species that are known high-level ACH producers [9,13]. Furthermore, the association was independent of the total salivary bacterial count, alcohol intake frequency, and other important health characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oral cavity is the first part of the digestive tract, which has contact with high-and low-concentrated alcohol. It can also be affected by ethanol metabolites [3]. Alcohol-based mouthwashes remain in longer contact with the oral cavity than alcoholic beverages when an alcoholic beverage is ingested.…”
Section: Introductionmentioning
confidence: 99%